Ergonomic Assessment Of Firefighting Activities And Musculoskeletal Disorders Using Inertial Measurement Unit Motion Capture Method - Yunus, Muhamad Nurul Hisyam (2023)
Back injury is a common musculoskeletal injury reported among firefighters due to their nature of work and personal protective equipment (PPE). The work nature associated with manual handling like lifting and carrying loads increases firefighters’ risk of back injury. The objective of this study was to identify the significant factor that contributes to the risk of back injury; analyze angle deviation and angular acceleration and categorize the risk of motion in selected firefighters’ activities. A set of questionnaires was used to identify the prevalence of musculoskeletal pain experienced by 19 firefighters. Inertial measurement unit (IMU) motion capture has been used in this study to record the body angle deviation and angular acceleration of 19 firefighters. The rapid entire body assessment (REBA) was used to quantify the level of risk from the selected firefighters’ activities. This study has selected lifting, walking with load, and climbing with load activities from firefighters’ work procedures to be analyzed. The result of the research shown that 63% of firefighters reported lower back pain during work which the three significant factors responsible for back injuries among firefighters has been identified; their activities, use of Personal Protective Equipment (PPE) and demographic backgrounds. The result of ergonomic assessment by using REBA shows that the risk level is at high risk for all selected activities.